2018
DOI: 10.1371/journal.pone.0200788
|View full text |Cite
|
Sign up to set email alerts
|

Gender equality in sickness absence tolerance: Attitudes and norms of sickness absence are not different for men and women

Abstract: Previous research offers limited understanding as to why sickness absence is higher among women than among men, but attitudes and norms have been suggested as plausible explanations of this gender gap. The purpose of the present study is to examine whether the gender gap in sickness absence reflects gender differences in sickness absence attitudes or gendered norms of sickness absence in society. The analyses are based on data from a factorial survey experiment covering 1,800 male and female employed responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 51 publications
1
14
0
5
Order By: Relevance
“…In a previous article, we found that respondents were equally lenient or restrictive with regard to sickness absence irrespective of whether the person described in a vignette was female or male [15]. Similar results based on direct survey questions rather than case descriptions were reported in a study of employees in social security offices [14]. The results above show that this conclusion holds even for a broad sample of managers in Norwegian establishments.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In a previous article, we found that respondents were equally lenient or restrictive with regard to sickness absence irrespective of whether the person described in a vignette was female or male [15]. Similar results based on direct survey questions rather than case descriptions were reported in a study of employees in social security offices [14]. The results above show that this conclusion holds even for a broad sample of managers in Norwegian establishments.…”
Section: Discussionsupporting
confidence: 85%
“…Less is known about the importance of attitudinal and cultural factors, such as a possibly greater social acceptance of women's than men's sickness absence [11]. A small number of empirical studies have compared men's and women's attitudes, largely indicating that women are not more inclined than men to accept absence taking in various situations [12][13][14]. A couple of studies have also addressed the related issue of whether the social norms with regard to absence taking are gendered and possibly less restrictive for women than for men, indicating that this is not the case, but the evidence is too limited to draw any conclusions [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concordantly, the found sex-difference regarding sick leave was only found if the GP was a woman. A recent Norwegian study on attitudes towards sick leave found that sick leave was more tolerated in workplaces heavily dominated by either one of the sexes [26]. Stressed women in general and in this study are often employed in the women-dominated service and health sectors while stressed men are less often employed in male-dominated workplaces [22].…”
Section: Comparison With Existing Literaturementioning
confidence: 79%
“…Undersøkelsesdesignet gjorde det videre mulig å se på om synet på sykefravaer varierte avhengig av om personen som ble beskrevet var en kvinne eller en mann, det vil si om kvinner og menn ser ut til å møte ulike forventninger fra omgivelsene. Dette var det ikke tegn til (Løset, Dale-Olsen, Hellevik, Mastekaasa, von Soest & Østbakken 2018).…”
Section: Tidligere Forskningunclassified